The Influence of Human Resources, Business Scale, Business Age, Accounting Training and Education Level on the Use of Accounting Information in MSMEs in Kudus Regency - Damayanti, Putri Amelia; Mulyanto, Mulyanto; Afifi, Zaenal (International Journal of Contemporary Sciences (IJCS), 2024)
This study seeks to empirically examine the impact of human resources, business size, business age, accounting training, and education level on the utilization of accounting information among MSMEs in Kudus Regency. The research employed purposive sampling, gathering data from a sample of 393 respondents. Multiple linear regression analysis was conducted using SPSS 25. The findings indicate that human resources, business size, business age, accounting training, and education level positively influence the use of accounting information in MSMEs.